Impacts of Climatic Variation on the Growth of Black Spruce Across the Forest-Tundra Ecotone: Positive Effects of Warm Growing Seasons and Heat Waves Are Offset by Late Spring Frosts - Moreau, Guillaume; Chagnon, Catherine; Auty, David; Caspersen, John; Achim, Alexis (Frontiers in Forests and Global Change, 2020)
Climate strongly limits the physiological processes of trees near their range limits, leading to increased sensitivity of growth to climate. Northeastern North America is experiencing one of the most rapid rates of warming on the planet, so the growth of trees near the northern treeline represent a key indicator of forest responses to climate change. However, tree-ring series and corresponding climatic data are scarce for high northern latitudes, resulting in a lack of studies on growth-climate relationships focused on this region. Using daily climatic data, we identified trends in growing season heat accumulation and the intensity of acute climatic events over the last several decades in the southern and the northern parts of the forest-tundra ecotone in northeastern North America, and investigated their influence on black spruce radial growth. We found that black spruce trees responded positively to the increase in growing season temperatures and heat wave intensity, suggesting that growth is currently limited by suboptimal temperatures. While tree growth in the southern region generally benefited from warm spring temperatures, the increasing intensity of thaw-freeze events reduced tree growth in the northern region and increased probability of abrupt growth decline. In this region, thaw-freeze events offset approximately half of the additional growth that would otherwise occur over the course of a warm growing season. This vulnerability of northern trees may result from local adaptations to short growing seasons and could be exacerbated by the increasing trend of thaw-freeze events intensity that prevailed in the north. Overall, our results highlight the need to explicitly incorporate acute climatic events into modeling efforts in order to refine our understanding of the impact of climate change on forest dynamics.